REPRESENTING AND REPETITION: VICTOR GOLLANCZ'S IN DARKEST GERMANY AND THE METONYMY OF SHOES. (October 2016) - Medhurst, Jessica
ABSTRACT: Victor Gollancz's book, In Darkest Germany (1947), is compiled from letters written and photographs taken during his six‐week visit to the British Zone of Occupation in 1946, and provides a counter to the official British political narrative about the occupation of Germany. This article examines Gollancz's text in the light of more recent theories of photography and of childhood as constructions in order to address his claim that photography is at 'a long remove' from what he saw in post‐war Germany, and to discuss the implications this has for our understanding of the German war child. It situates close readings of Gollancz's writing about photography and photographs of '[s]chool children's shoes in Hamburg and Düsseldorf' within the wider contexts of his socialism and the metonymy of children's shoes in post‐war Germany, in order to argue that he engages with sophisticated theoretical ideas about the insufficiency of photography and language as means of retrieving a lived reality in pursuance of his efforts to engage a politically apathetic public. The repetitiveness of his photographs of children's shoes positions them as standing in for the situation of German children generally in the aftermath of World War II, with the aim of making these conditions comprehensible to the British public. Underpinning the repetition is the representation of the war child, which seems to escape the issues of photography that Gollancz discusses but which ultimately confirms them. Das Buch In Darkest Germany (1947) von Victor Gollancz enthält Briefe und Fotografien, die 1946 während Gollanczs sechswöchiger Reise durch die britische Besatzungszone entstanden; es bietet einen Gegendiskurs zum offiziellen britischen Diskurs über die Besatzung Deutschlands. Dieser Aufsatz analysiert Gollanczs Text mit Hilfe neuerer Theorien zum Konstruktionscharakter von Fotografie und Kindheit, um die Implikationen von Gollanczs Einsicht, die Fotografie sei 'weit entfernt' von dem, was er im Nachkriegsdeutschland gesehen habe, für unser Verständnis des deutschen Kriegskindes zu erhellen. Der Aufsatz stellt die Analyse von Gollanczs Äußerungen über den Repräsentationscharakter von Fotografie in den Kontext seiner sozialistischen Ideale. Dabei wird argumentiert, dass Gollancz sich auf eine komplexe theoretische Auseinandersetzung mit der Unzulänglichkeit von Fotografie und Sprache, das historisch Tatsächliche zu erfassen, einlässt, während er gleichzeitig eine politisch desinteressierte Öffentlichkeit mit seiner Arbeit aufrütteln will. Der Wiederholungscharakter seiner Fotografien von Kinderschuhen positioniert diese als Repräsentation der Lebensbedingungen deutscher Kinder in der Nachkriegszeit, um diese Verhältnisse der britischen Öffentlichkeit verständlich zu machen. Die Darstellung des Kriegskindes scheint von den Fragen, die Gollancz anhand der Fotografien diskutiert, zunächst nicht betroffen, wird jedoch von diesen eingeholt.